The first squamulose Thelocarpon species (Thelocarpaceae, Ascomycota) discovered in the biological soil crusts in the Bolivian Andes - Flakus, Adam; Kukwa, Martin (Phytotaxa, 2014)
Thelocarpon andicola, a new terricolous species from the tropical Andes in Bolivia is described in this paper. This is the first member of the genus with squamulose to placodioid and yellow pruinose thallus, which is further characterized by non-amyloid hymenial gel, branched paraphyses, amyloid asci without visible mass axiale and broadly ellipsoidal ascospores.